Discursos sobre amor e sexo: análise nas revistas Men’s Health e Women’s Health - (:unkn) unknown (Universidade Federal do Pampa, 2011)
This article analyzes the discursive construction of love and sex and their relationship with female and male genders, using, as object of analysis, discourses from Men‟s Health e Women‟s Health magazines. From Michel Pêcheux‟s Discourse Analysis, the purpose is to verify how certain linguistic marks tells of ideological positions that distinct said masculine and feminine roles and identities and how discourses present in these magazines are determinate and reproduced in society and contribute to the establishment of ideologies related to gender.
Keywords: Letras; Literatura; Amor; Sexo; Análise do discurso; Ideologia; Análise crítica; Linguística; Literature; Letters; Love; Sex; Speech analysis; Ideology; Critical analysis; Linguistics